The EFFECTIVENESS OF THE SITZ BATH METHOD WITH BOILING BINAHONG LEAVES IN HEALING PERINEUM WOUNDS IN POST PARTUM MOTHERS IN SUKANAGALIH CIANJUR YEAR 2023 - Vivi Silawati; Putri Azzahroh; Diena Hannifa (International Health Sciences Journal, 2024)
Abstract Background:Perineal rupture is a condition that occurs quite often during normal childbirth. One of the factors that influence the wound healing process is perineal care, there are several methods, one of which is the sizt bath method with boiled binahong leaves. Objective:To determine the effectiveness of the binahong leaf sitz bath method for healing perineal wounds in post partum mothers in Sukanagalih Cianjur 2023. Methodology:Researchers used a quasi-experimental design with a pretest and posttest with control group design. The sample in the study was 30 post partum mothers consisting of 15 respondents who were given intervention and 15 respondents who were not given intervention. The sampling technique used Total Sampling, the sizt bath method with binahong leaves given for 7 days in the morning. The research instrument in the form of an observation sheet was carried out twice before and after the intervention was given. The analysis used was Paired t-test for tests within groups and independent t-test for tests between groups. Research result:In the intervention group the binahong leaf sizt method before and after the intervention was 4.60 and 1.67 with Paired t-test results <0.05. In the control group, the before and after results were 4.27 and 2.67 with Paired t-test results <0.05. Independent t-test results 0.035 <0.05. It can be concluded that there are differences between the experimental and control classes Conclusion:The Sizt bath method of binahong leaves has an effect that can accelerate wound healing in post partum mothers Keywords:Binahong leaves, Wound Healing, Sizt bath